SIMULATION OF TWO INTERACTING GALAXIES NGC3395 AND NGC3396 - Rasheed, Mariwan (Iraqi Journal of Science, 2024)
In the present work the two interacting galaxies NGC3395 and NGC3396 were simulated by means of N-body simulation using Intergalactic Gravitational Motion Simulator IGMS code with 500 particles. The structure and the geometrical positions of each galaxy and their contents were found from the time before the interaction. It was also found that the interaction caused the distortion of the shape and construction of tidal tails of the galaxy NGC3395. The simulation image matches with the images of the two galaxies observed by the telescopes.